Eating in Isaiah : approaching the role of food and drink in Isaiah's structure and message - Abernethy, Andrew T. (Biblical Interpretation Series, 2014)
In Eating in Isaiah Andrew Abernethy employs a sequential-synchronic approach to explore the role of eating in the structure and message of the book of Isaiah. By focusing on 'scaffolding' chapters (Isaiah 1; 36-37; 55; 65-66), avenues open for exploring how eating operates within the major sections of Isaiah and how the motif enhances the book's coherence. Furthermore, occurrences of eating in Isaiah create networks of association that grant perspective on significant topics in the book's message, such as Zion, YHWH's kingship, and YHWH's servants. Amidst growing scholarly interest in food and drink within biblical literature, Eating in Isaiah demonstrates how eating can operate at a literary level within a prophetic book.